Pengaruh BOPO dan NPL terhadap Financial Suistainability pada PT BPR Artha Parama periode 2016-2023 - hidayati, nurul; Prasetya, Bangun Putra (Jurnal USAHA, 2024)
Banking Companies such as PT BPR Artha Parama experienced an increase in NPL ratios after the emergence of the Covid 19 pandemic, although currently the pandemic has passed, Banking Companies are still experiencing difficulties to reduce NPL ratios. NPLs at banks can experience a significant increase because the covid pandemic has resulted in a decrease in income from debtors with businesses in various sectors including tourism, trade, agriculture, fisheries, etc. The debtor must reschedule his credit or restructure so that the credit quality becomes less good. This study aims to determine the Effect of BOPO and Non Performing Loan (NPL) on Financial Sustainability at PT BPR Artha Parama for the 2016-2023 period. This study used a quantitative approach. The study population is PT BPR Artha Parama with an observation period of 2016 to 2023. The sample selection technique uses the purposive sampling method. The data analysis method used is multiple linear regression analysis. The results showed that BOPO had a significant effect on the Financial Sustainability Ratio, while Non-Performing Loans (NPL) did not have a significant effect on the Financial Sustainability Ratio.